Design and fabricate mini lathe machine - Nik Azman Abadi, Nik Daniel Haziq; Mohd Yusof, Ab Aziz (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
Lathe machines are commonly used in workshops for various machining operations such as cutting and turning, with different types including CNC, engine, and bench lathes. These machines consist of three main components: the headstock, tailstock, and bed. A key challenge in this project is designing the bed of a mini lathe machine, as it must be sufficiently heavy to stabilize the structure and prevent excessive shifting. The machine will be designed specifically for machining wood, which is softer and easier to shape than metal but produces significant waste in the form of shavings and dust. The project has two main objectives: first, to design a prototype of a mini lathe machine using SolidWorks, and second, to fabricate the machine based on the developed design. Engineering analysis will identify high-stress areas and determine the factor of safety, while detailed design drawings will provide a clear visualization of the machine's components and assembly.